MEMBANGUN KESADARAN KRITIS BAHASA JAWA MELALUI MODEL PEMBELAJARAN PEMAKNAAN DI SEKOLAH DASAR - Endang Sri Maruti; Dyo Ilham Alif Utomo (SITTAH: Journal of Primary Education, 2023)
Until now, learning Javanese from elementary school to high school is only a teaching routine, namely only providing material according to the curriculum. This study aims to develop a learning model of meaning to build students' critical awareness in Javanese. This research refers to the 4-D development model. The research subjects were public elementary school students in Madiun City. Data were collected by observation techniques, tests, questionnaires, and data analysis using descriptive statistical techniques. The study results showed that the Javanese language learning models and tools researched and developed are valid, practical, and effective and can increase critical awareness of moral sensitivity, thinking skills, and mastery of concepts in elementary school students. The meaning learning model combines problem-based learning with ethical aspects of learning that can increase students' critical awareness of the Javanese language.